Peran Financial Teknologi Digital melalui Market Place dalam Meningkatkan Pendapatan UMKM Canting Buana Kreatif Padang Panjang Sumatera Barat - Sugiyanto, Sugiyanto; Kartolo, Rachmat (Jurnal PKM Manajemen Bisnis, 2024)
The role of financial technology is considered to be at the forefront of digital market developers through market places in increasing the income of Business Canting Buana Creative Padang Panjang, West Sumatra in increasing the productivity of buying and selling or transactions. This sector is what determines the increasing growth of the batik industry today. The culture of providing services with fintech via applications on smartphones is no longer difficult. The impact will also increase sales. This trend has actually started with shifts in society today. Fintech has the potential to encourage the growth of the MSME sector by making transactions. The PKM method through preparation, of course, cannot be done alone, especially not all MSMEs understand the whole problem, so business actors need to be assisted and accompanied. The community service program held at business Canting Buana Creative Padang Panjang, West Sumatra, aims to train in the application and role of digital financial technology and be guided in preparing financial reports using Microsoft Excel applications and digital technology. This activity is carried out in a sustainable, measurable manner and through a monitoring and evaluation process to measure the achievement of targets and expected outcomes, namely enabling MSME players to prepare financial reports to increase the competitiveness of Business. The results of PKM using the financial media technology of Canting Buana Creative Batik Padang Panjang West Sumatra can predict the use of Fintech accounting, various types of bookkeeping reports, other types and components of financial reports. Business Canting Buana Creative Batik Padang Panjang West Sumatra can record financial transactions through the market place using Microsoft Excel means of the accounting cycle. Business Canting Buana Creative Batik Padang Panjang, West Sumatra can carry out financial reporting in an orderly and periodic manner. Community empowerment for actors and competitiveness in Canting Buana Creative Batik Padang Panjang, West Sumatra Business increases and business sustainability increases.